Agricultural mantra culture in the study of the Melak Pare Manuscript - Supendi, Usman; Solehudin, Solehudin; Sopiah, Eva; Nuraidah, Syifa; Arsyad, M Fikri; Hambaliana, Dandie (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This study aims to explore the physical structure and content of the Melak Pare manuscript, which documents the agrarian traditions of the Sundanese people within the framework of local and Islamic spirituality. Employing a historical methodology that includes heuristics, verification, interpretation, and historiography, the data were gathered through literature reviews and field research on the original manuscript housed in the Sri Baduga Museum, Bandung. The findings reveal that the manuscript is written in Arabic Pegon script on fragile European paper now preserved with Japanese tissue. The content consists of agricultural mantras and prayers structured around stages of rice farming rituals—from hoeing and seed sowing to planting, maintenance, and harvesting. The inclusion of istighfar, shalawat, and invocations of Dewi Sri (Nyimas Puhaci Sangiyang Sri) demonstrates cultural assimilation between Islam and local beliefs. Symbolic references to cardinal directions, bodily movements, and ritual timing reflect a rich Sundanese agrarian cosmology imbued with spiritual significance. This research contributes to the preservation of local philological heritage, revitalization of agro-spiritual values, and advancement of interdisciplinary approaches to traditional manuscript studies. Contribution: This study contributes to the preservation of local philological heritage by documenting the physical and textual features of the Melak Pare manuscript, revitalizes agro-spiritual values by highlighting the integration of Sundanese agrarian traditions with Islamic spirituality.